Hypergamy, cross-boundary marriages, and family behavior - Yoram Weiss; Junjian Yi; Junsen Zhang (Institute for the Study of Labor (IZA), 2013)
We study the rise in marriages between residents of HK and China following the handover of HK to China in 1997. Cross-boundary marriages accounted for almost half the marriages registered in HK in 2006. Because of large differences in male income between China and HK, marriages of HK men with Mainland women outnumbered those of HK women with mainland men sevenfold. Following the handover, HK women had lower marriage, higher divorce and higher emigration rates. These outcomes are predicted by our matching model and contradict the hypothesis that cross-boundary marriages were driven by rising education of HK women.
Keywords: F22; J11; J12; 330; one-way permit; hypergamy; cross-boundary marriage; family behavior